Síntese estendida: uma investigação histórico-filosófica - Reversi, Luiz Felipe [UNESP] (2015)
Currently several emerging issues are questioning the validity and scope of the current conceptual framework of evoluationary biology, known as Modern Synthesis, and expansions of this frame are being discussed, leading to a new conceptual framework called Extended Synthesis, since it seeks to expand rather than refute the Modern Synthesis. There discussions have also raised questions about the epistemology and the historical nature of evolutionary biology, in this sense we seek a theoretical framework that could philosophically the development of evolutionary ideas and theories in the history of biology as well as explain the current process of expandion of the Modern Synthesis. Thus, we performed a philosophical analysis of the history of the evolutionary biology through a Bachelardian referential, and we observed a progressive rationalism in this historical process, being consistent with the epistemological profile model proposed by Bachelard. After this analysis we seek to investigate how it could contribute to the teaching of evolution plays a central role both for biology and for his teaching, combining their different areas and giving them direction. Also the bachelardian theory of epistemological profiles has the unique ability to closely relate the historical and philosophical development of a concept to the psychological development of the same concept in it's teaching-learning process. We found that the teaching of evoluation has several problems such as - Teachers difficulties in dealing with religious conceptions of the students; Finalists and Teleological views of evolution brought by students and teachers as well; Fragmented teaching of biology content; Lack of theoretical bases for teachers to work with the history of science and to use evolution as an integrating axis; Strictly genecentric conception of biological evolution; Teaching of evolution restricted to Lamarck's and Darwin's ideas and opposition between them - Most...